Ten-year Retrospective Chart Review of Postneonatal Tetanus at Semiurban Tertiary Care Teaching Hospital of Gujarat, Western India - Rajesh N Pankhaniya; Nili Mehta; Kapil Jetha; Krutika R Tandon (Pediatric Infectious Disease)
Background: Despite being a vaccine-preventable disease, tetanus continues to cause considerable morbidity and mortality, especially among children. In India, the incidence of non-neonatal tetanus has decreased from 23,356 cases in 1990 to 4,946 cases in 2017. Yet, it continues to pose a threat in both urban and rural settings, and it remains a public health issue in regions with low immunization coverage. Here, we are reporting a 10-year chart review of postneonatal tetanus for its clinical profile and outcome. Materials and methods: After Institutional Ethics Committee approval with waiver of consent, this retrospective study reviewed the data of all indoor pediatric patients between 1 month and 18 years from 2014 to 2023 (10 years) who had a diagnosis of tetanus from hospital records. A record of 26 patients with tetanus was retrieved from the Hospital Management Information System (HMIS) and patient files. All pertinent details were collected and analyzed using STATA 14.2. Results: Out of all 26 cases of tetanus, males were 18 (69.2%). Twenty-two (84.6%) patients were between 5 and 18 years, and only four (15.4%) were under 5 years of age. Successful discharge occurred in 19 patients, mortality in three patients, and discharge against medical advice/abscond in four patients. Twenty-two (84.6%) patients were from rural areas, and 18 (69.2%) were postinjury cases. Ten patients (38.46%) were unimmunized, whereas 15 (57.69%) were partly immunized with tetanus toxoid (TT). Seven from the unimmunized and eight from the partly immunized category had severe tetanus. The incubation period ranged from 1 to 15 days, with a median (Q1, Q3) of 4.52, 7 days. The duration of the hospital stay ranged from 1 to 78 days, with a median (Q1, Q3) of 17.5 (8.5, 32) days. Trismus and spasms were present in all patients. Among other symptoms, difficulty in swallowing, fever, autonomic instability, and retention of urine/oliguria were present in 10, 8, 7, and 3 patients, respectively. Among expired patients, cellulitis with septic shock, pneumonia, and acute kidney injury (AKI) were major issues. A mechanical ventilator was needed in 14 (53.85%) patients. Fifteen patients (57.7%) were tracheostomized. No association of mortality and severity was found when compared to age, gender, mode of infection, need for a mechanical ventilator, duration of spasms, immunization status, tetanus immunoglobulins, etc., in this limited sample size. Conclusion: Posttraumatic severe tetanus is still prevalent in older and unimmunized/partially immunized children, though it is preventable 100%. Mortality was also high in severe tetanus requiring mechanical ventilation and pediatric intensive care unit (PICU) management.